Subtract them both and then u will get your answer
Answer:
(1) ![g[f(x)]=\frac{8x-1}{12x-4}](https://tex.z-dn.net/?f=g%5Bf%28x%29%5D%3D%5Cfrac%7B8x-1%7D%7B12x-4%7D)
(2) ![g^{-1}(x)=\frac{x+1}{(3x-2)}](https://tex.z-dn.net/?f=g%5E%7B-1%7D%28x%29%3D%5Cfrac%7Bx%2B1%7D%7B%283x-2%29%7D)
(3) ![x=\frac{9+\sqrt{129} }{6}, \frac{9-\sqrt{129} }{6}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B9%2B%5Csqrt%7B129%7D%20%7D%7B6%7D%2C%20%20%5Cfrac%7B9-%5Csqrt%7B129%7D%20%7D%7B6%7D)
Step-by-step explanation:
Given functions f(x) = (4x-1)
are ![g(x)=\frac{2x+1}{3x-1}](https://tex.z-dn.net/?f=g%28x%29%3D%5Cfrac%7B2x%2B1%7D%7B3x-1%7D)
(1) ![g[f(x)]=\frac{2(4x-1)+1}{3(4x-1)-1}](https://tex.z-dn.net/?f=g%5Bf%28x%29%5D%3D%5Cfrac%7B2%284x-1%29%2B1%7D%7B3%284x-1%29-1%7D)
![=\frac{8x-2+1}{12x-3-1}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B8x-2%2B1%7D%7B12x-3-1%7D)
![=\frac{8x-1}{12x-4}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B8x-1%7D%7B12x-4%7D)
(2) for
, rewrite the function g(x) in terms of an equation
![y=\frac{2x+1}{3x-1}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B2x%2B1%7D%7B3x-1%7D)
Substitute y in place of x and x in place of y, then solve for y.
![x=\frac{2y+1}{3y-1}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2y%2B1%7D%7B3y-1%7D)
(3y-1)x = 2y+1
3xy - x = 2y + 1
3xy - 2y = x + 1
y(3x-2) = x + 1
![y=(\frac{x+1}{3x-2} )](https://tex.z-dn.net/?f=y%3D%28%5Cfrac%7Bx%2B1%7D%7B3x-2%7D%20%29)
⇒ ![g^{-1}(x)=\frac{x+1}{(3x-2)}](https://tex.z-dn.net/?f=g%5E%7B-1%7D%28x%29%3D%5Cfrac%7Bx%2B1%7D%7B%283x-2%29%7D)
(3) ![f[g(x)]=(x-1)](https://tex.z-dn.net/?f=f%5Bg%28x%29%5D%3D%28x-1%29)
![f[g(x)]=4[\frac{2x+1}{3x-1}] =(x-1)](https://tex.z-dn.net/?f=f%5Bg%28x%29%5D%3D4%5B%5Cfrac%7B2x%2B1%7D%7B3x-1%7D%5D%20%3D%28x-1%29)
⇒ ![\frac{(8x+4)-(3x-1)}{3x-1}=(x-1)](https://tex.z-dn.net/?f=%5Cfrac%7B%288x%2B4%29-%283x-1%29%7D%7B3x-1%7D%3D%28x-1%29)
⇒ ![\frac{8x-3x+4+1}{3x-1}=(x-1)](https://tex.z-dn.net/?f=%5Cfrac%7B8x-3x%2B4%2B1%7D%7B3x-1%7D%3D%28x-1%29)
⇒ ![\frac{5x+5}{(3x-1)}=(x-1)](https://tex.z-dn.net/?f=%5Cfrac%7B5x%2B5%7D%7B%283x-1%29%7D%3D%28x-1%29)
⇒ ![5x+5=(3x-1)(x-1)](https://tex.z-dn.net/?f=5x%2B5%3D%283x-1%29%28x-1%29)
⇒ ![5x+5=3x^2-3x-x+1](https://tex.z-dn.net/?f=5x%2B5%3D3x%5E2-3x-x%2B1)
⇒ ![5x+5=3x^2-4x+1](https://tex.z-dn.net/?f=5x%2B5%3D3x%5E2-4x%2B1)
⇒ ![3x^2-9x-4=0](https://tex.z-dn.net/?f=3x%5E2-9x-4%3D0)
⇒ ![x=\frac{9\pm\sqrt{(-9)^2-4(-4)\times3} }{2\times3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B9%5Cpm%5Csqrt%7B%28-9%29%5E2-4%28-4%29%5Ctimes3%7D%20%7D%7B2%5Ctimes3%7D)
![x=\frac{9\pm\sqrt{81+48} }{6}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B9%5Cpm%5Csqrt%7B81%2B48%7D%20%7D%7B6%7D)
![x=\frac{9\pm\sqrt{129} }{6}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B9%5Cpm%5Csqrt%7B129%7D%20%7D%7B6%7D)
![x=\frac{9+\sqrt{129} }{6}, \frac{9-\sqrt{129} }{6}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B9%2B%5Csqrt%7B129%7D%20%7D%7B6%7D%2C%20%20%5Cfrac%7B9-%5Csqrt%7B129%7D%20%7D%7B6%7D)
Answer:
P= 20
Step-by-step explanation:
to get p by its self we do the opposite which in this case is multiplication 4x4 cancel each other 5(4) = 20
Answer:
![\huge \boxed{K=20}\checkmark](https://tex.z-dn.net/?f=%5Chuge%20%5Cboxed%7BK%3D20%7D%5Ccheckmark)
B. 20
Step-by-step explanation:
<em>First, you divide by 5 from both sides of equation.</em>
<em>
</em>
<em>Simplify, to find the answer.</em>
<em>
</em>
<em>
, which is our answer.</em>
38 42 34 54
Step-by-step explanation:
7have the best mayonnaise bianco babi naive albino pig is this real or not be a posible and I am a great day for 53feet